Initial orientation of the fretting fatigue cracks in shrink-fit connection specimens - Ciro Santus (Fracture and Structural Integrity)
The bending configuration of shrink-fitted connection fretting fatigue tests causes a fluctuation of the contact pressure and in turn a more favourable condition for shear, rather than tensile, crack initiation. According to the classification Type I (shear) and Type II (tensile) fretting cracks, the type II was only observed for the tests with no surface enhancement, which experienced the lowest fretting strength and then a reduced pressure fluctuation effect. The crack initial direction was predicted as the critical plane orientation undergoing the maximum FS stress parameter, for the shallow type I shear cracks. If the critical plane is searched at the fretting hot-spot, the incorrect outward direction is obtained, since the orthogonal direction, with the same shear stress amplitude, experiences a more compressive maximum normal stress. On the contrary, with the application of the Point Method, taking the stress location at half the critical distance and by following the potential critical plane, a higher shear stress along the inward direction is obtained. The more compressive stress below the contact can therefore be compensated, and then the inward shallow direction is correctly predicted.